2018
DOI: 10.1016/j.jtho.2018.07.094
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Pemetrexed in Patients with Recurrent Thymoma and Thymic Carcinoma

Abstract: Pemetrexed is an active agent in this heavily pretreated population of patients with recurrent thymic malignancies, especially thymoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…Clinical features and histology are different in IT and TC and recent improved genetic, epigenetic and transcriptomic analyses revealed distinct molecular bases for these disease [12,13]. Correspondingly, previous studies and the present study showing different outcomes for IT and TC are probably due to their histological and biological differences [6,14].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Clinical features and histology are different in IT and TC and recent improved genetic, epigenetic and transcriptomic analyses revealed distinct molecular bases for these disease [12,13]. Correspondingly, previous studies and the present study showing different outcomes for IT and TC are probably due to their histological and biological differences [6,14].…”
Section: Discussionsupporting
confidence: 69%
“…However, no standard treatment has been established for previously-treated IT and TC because there have been very few prospective studies in such patients. In recent phase II trials, sunitinib, everolimus, pemetrexed and pembrolizumab have shown beneficial effects [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with advanced thymic carcinoma are usually treated with palliative chemotherapy or supportive care; however, there is little evidence in support of chemotherapy because of the rarity of this tumor. Furthermore, there are very few reports about second-line chemotherapy for patients with previously treated advanced thymic carcinoma, and these are all from retrospective studies with small sample sizes (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Owing to the limited number of studies performed, it is difficult to select a chemotherapy regimen for these patients in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…
We read with interest the article by Gbolahan et al 1 about a phase II study testing pemetrexed in a patient with recurrences of thymoma and thymic carcinoma. In particular, they showed encouraging results in terms of response rate with use of this antifolate agent after different lines of previous chemotherapy, with a response rate of about 25%.In their conclusion, Gbolahan et al 1 underline the fact that the potential role of this agent as first-line therapy or in association with other agents may be tested, as is indicated also for other malignancies such as lung cancer or mesothelioma.
…”
mentioning
confidence: 99%
“…
We read with interest the article by Gbolahan et al 1 about a phase II study testing pemetrexed in a patient with recurrences of thymoma and thymic carcinoma. In particular, they showed encouraging results in terms of response rate with use of this antifolate agent after different lines of previous chemotherapy, with a response rate of about 25%.In their conclusion, Gbolahan et al 1 underline the fact that the potential role of this agent as first-line therapy or in association with other agents may be tested, as is indicated also for other malignancies such as lung cancer or mesothelioma. 2 With regard to this consideration, we would ask Gbolahan et al 1 whether they intend to utilize the possibility of maintenance therapy after complete or partial response after first-line chemotherapy or as an independent initial treatment.Moreover, with regard to thymomas, we would ask Gbolahan et al 1 whether they think that pemetrexed may also have a role in induction protocols.
…”
mentioning
confidence: 99%